Impact of highly active antiretroviral therapy (HAART) on body composition and other anthropometric measures of HIV-infected women in a primary healthcare setting in KwaZulu-Natal : a pilot study - Esposito, Francesca (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.